Nanog is a promising chemoresistant stemness marker and therapeutic target by iron chelators for esophageal cancer. Issue 2 (5th April 2021) - Narusaka, Toru; Ohara, Toshiaki; Noma, Kazuhiro; Nishiwaki, Noriyuki; Katsura, Yuki; Kato, Takuya; Sato, Hiroaki; Tomono, Yasuko; Kikuchi, Satoru; Tazawa, Hiroshi; Shirakawa, Yasuhiro; Matsukawa, Akihiro; et al.
Abstract: Esophageal cancer is a disease showing poor prognosis. Although combination chemotherapy using cisplatin (CDDP) and 5‐fluorouracil is standard for unresectable esophageal cancer, the response rate is 35%. Cancer stem cells (CSCs) and inflammation are reportedly responsible for the poor prognosis of esophageal cancer. However, comprehensive analyses have not been conducted and proposals for progress remain lacking. Iron is known to be a key factor in the stemness of CSCs. Our study focused on the therapeutic potential of iron control using iron chelators for CSCs in esophageal cancer. Among 134 immunohistochemically analyzed cases, Nanog expression was high in 98 cases and low in 36 cases. High Nanog expression correlated with low overall and disease‐free survivals. The iron chelators deferasirox (DFX) and SP10 suppressed the proliferation and expression of stemness markers in TE8 and OE33 cells. DFX and SP10 did not induce compensatory interleukin (IL)‐6 secretion, although CDDP did result in high induction. Moreover, BBI608 and SSZ, as other CSC‐targeting drugs, could not suppress the expression of stemness markers. Overall, Nanog expression appears related to poor prognosis in esophageal cancer patients, and inhibition of stemness and compensatory IL‐6 secretion by iron chelators may offer a novel therapeutic strategy for esophageal cancer. Abstract : What's new? IL‐6 correlates with poor prognosis in esophageal cancer. However, biomarkers specifically related to esophageal cancer stem cells remain to be established. In this study of radical esophagectomy patients, high expression of the stemness marker Nanog correlated with low overall survival in the neoadjuvant therapy group only. Iron chelators, but not other cancer stem cell‐targeting drugs, suppressed Nanog expression without compensatory IL‐6 secretion. Altogether, Nanog could potentially be used as a marker of resistance to conventional 5‐FU and/or cisplatin chemotherapy in esophageal cancer patients, and inhibition of stemness and compensatory IL‐6 secretion by iron chelators could represent a novel therapeutic strategy.